Immunotherapy for epithelial tumors of the thymus - O. I. Kit; D. A. Kharagezov; Yu. N. Lazutin; E. A. Mirzoyan; A. G. Milakin; O. N. Stateshny; T. G. Ayrapetova; I. A. Leyman; M. A. Gappoeva; V. N. Vitkovskaya; K. D. Iozefi; M. A. Khomidov (Южно-Российский онкологический журнал)
Thymomas and carcinomas of the thymus gland, also known as epithelial tumors of the thymus (TT) are rare malignant neoplasms, but are the most common solid tumors of the anterior mediastinum. The incidence does not exceed 1.3–1.7 per million inhabitants per year. In Europe, about 1,500 new cases are registered annually, and the average age of patients is around 40–50 years.Originating from the epithelial component of the thymus, the primary lymphoid organ, they are accompanied by a high risk of developing autoimmune disorders due to their unique biology. Indeed, up to 30 % of TETS patients suffer from autoimmune disorders (AID), the most common of which is myasthenia gravis (MG). AID are detected not only during the diagnosis of a tumor, but also during follow-up. With rare exceptions, there are no specific targets for targeted therapy in TETS. Immune checkpoint inhibitors (ICIs) halt the ability of tumor cells to evade immune surveillance, enhancing their killing. Unprecedented achievements of immunotherapy (IT) in the treatment of metastatic non-small cell lung cancer (NSCLC) and melanoma have made it reasonable to study the effectiveness of prescribing ICI in patients with TETs. The prevalence of AIR in different morphological subtypes of TETs may influence the decision to conduct IT due to the increased risk of toxicity. The review summarizes current data on the effectiveness of IT in thymoma and thymus cancer (TC) and discusses several unresolved problems associated with the use of ICI in TETs.The purpose of this review is to present up-to-date data on the issue under discussion and possible prognostic biomarkers for IT, and to highlight the problems associated with autoimmune disorders (AID). In our opinion, a deep understanding of the molecular genetic and immune landscape of thymus epithelial tumors and the interaction of ICI with the immune system is the key to improving the effectiveness and preventing the side effects of autoimmune IT. A comprehensive solution to existing problems will undoubtedly open up new possibilities for the drug treatment of this rare and difficult disease.